"Case-study" method as a component of training under distance learning conditions in higher medical educational institutions - Kucher, T. V.; Vasylenko, G. V.; Кучер, Тетяна Володимирівна; Василенко, Гліб Володимирович (My University, 2020)
The task of modern medical education is the formation of professional orientation and competence of medical students, the ability to summarize and synthesize information in order to create the ability to accurately diagnose and prescribe adequate treatment, which corresponds to the form of the system adopted in Europe. To determine the level of professionalism and competence the most countries use the method of problem-based learning "Problem-based learning" (PBL) as a variant of another method - "Case based learning" (CBL), which has become widespread in many medical schools [1]. Problem-based learning (PBL) is a method of "active learning", which is a logical step to promote the synthesis and integration of fundamental knowledge into clinical thinking [2]. The essence of the "Case based learning" is the use of a methodological approach based on specific cases, which involves students to discuss specific scenarios that resemble or are usually real examples. Achieving a balance between the existing traditional methods of training and the "Western" system can be done through the involvement of modern practice-oriented approaches and technologies [3]. One of these is the "case-study" method, which focuses on the formation of the ability to act in situations where there is no unambiguous answer to the question, but there are several answers that can compete for the degree of veracity [4]. One of the possible options for implementing the method of problem-based learning in these conditions may be the use of tests of the minimum allowable competence (Minimum Competency Test) and qualification tests (mastery tests) [5].